A pilot study of the efficacy of the POLARGEN® ultrahigh-frequency electric field (40.68 MHz) radiofrequency device in the treatment of facial contouring. (3rd October 2017) - Kim, Miri; Lim, Jihong; Bae, Jung Min; Park, Hyun Jeong
ABSTRACT: Background : Various radiofrequency (RF) devices are used to treat skin laxity and face contouring, but few studies have examined ultrahigh-frequency (UHF) electric field (40.68 MHz) RF devices.Objective : To evaluate the efficacy and safety of a UHF electric field (40.68 MHz) RF device for skin tightening and face contouring.Methods : Ten patients each underwent four sessions of UHF electric field RF device treatment at 2-week intervals. Clinical improvement was evaluated with the patient satisfaction score using a six-point scale, and clinical photographs taken at every visit and 2 months after the RF treatment were assessed. Skin biopsies were obtained from one patient before the first treatment and immediately after the last treatment. Adverse reactions were recorded at every follow-up visit.Results : All patients were women with a mean age of 51.7 ± 7.2 years. The mean satisfaction score was 4.5 ± 0.9 immediately after the last treatment session. Cheek, jawline, and neck enhancement and tightening were apparent in all patients. Side effects were minimal, and there were no burns or major complications.Conclusions : The UHF electric field RF device was effective for skin tightening and facial contouring, without significant adverse reactions.